Ohmic contact characteristic of nanostructured titanium dioxide (TiO2) thin films anneal at different temperature: article / Mohd Azlan Mohamad Zainuddin - Mohamad Zainuddin, Mohd Azlan (2009)
This paper studied on the ohmic contact characteristics of nanostructured TiO2 thin films anneal at different temperature. The preparation of TiO2 solution used the Titanium (IV) butoxide as a precursor at concentration of 0.2M. TiO2 thin films were prepared by spin-coating technique and derived sol onto glass substrate, followed by an annealing at temperatures ranging from 350◦C to 550◦C. The result will be analyse on the I-V characteristics and observed it to get the ohmic contact by using gold, platinum and palladium as a metal contact. The influence of the annealing temperature on the electrical, structural and surface morphology of the thin film were characterize by using the I-V measurements, scanning electron microscope (SEM) and atomic force microscope (AFM). Due to the observation in electrical measurement at 550oC, platinum is the best metal contact compared to gold and palladium. This ohmic contact was observed by looking at the capability of metal contact delivering the required current with no voltage drop between the semiconductor and the metal.